Enhanced Methane Production from Pretreatment of Waste Activated Sludge by Economically Feasible Biocatalysts - Tae-Hoon Kim; Dayeong Song; Jung-Sup Lee; Yeo-Myeong Yun (Energies, 2023)
Crude hydrolytic extracellular enzymes (CHEEs) generated by a mixed culture of microorganisms during fermentation have a high potential as economically feasible biocatalysts for the hydrolysis of complex organic wastes. This study investigates the feasibility of CHEEs as substitutes for commercial enzymes based on a series of anaerobic batch tests for CH4 production fed by pretreated waste activated sludge (WAS). The results showed that cellulase presented the highest CH4 yield of 99.1 mL·CH4/g·COD of WAS among the samples pretreated with single commercial enzymes, with a yield 34% higher than that of the control sample. A higher diversity of commercial enzymes used in the pretreatment led to higher CH4 production from WAS. The sample pretreated with a mixture of four commercial enzymes (amylase + protease + cellulase + lipase, APCL) presented a CH4 yield of 216.0 mL·CH4/g·COD of WAS. The WAS prepared with CHEEs resulted in a CH4 yield of 211.9 mL·CH4/g·COD of WAS, which is comparable to the performance of the sample pretreated with APCL. The results of the batch tests using pretreated WAS for different APCL concentrations showed that the CH4 yield of WAS pretreated with CHEEs was comparable to the CH4 yield of 0.34 g·APCL/g·COD of WAS.